Malaria, desnutrición en niños e inseguridad alimentaria en sus hogares : una revisión (2009)
ABSTRACT: Malaria and household food insecurity are public health problems in Colombia that should be studied in an integrated approach. Objective: to describe the relationship between malaria and malnutrition, deficiencies of vitamin A, zinc and anaemia in children; and household food insecurity, as well as the effect of retinol, iron and zinc supplements on morbidity and mortality in children with malaria infection. Methodology: Medline and other databases were searched. Results: the articles showed that protein-caloric malnutrition and deficiencies of both vitamin A and Zinc increase morbidity and mortality associated to Malaria infection. Studies of the effects of micronutrient supplements on morbidity and mortality associated to Malaria caused by P. falciparum confirmed that vitamin A supplements’ may has a protective effect; studies of zinc on malaria are no conclusive, although it has other benefits; and supplement of iron could presents a deleterious effects, an it seems to be influenced by children age and if it is administer alone o combined with zinc. There is a strong relationship between Household food insecurity and malaria. Prevention of household food insecurity should contribute to decrease children malnutrition and to reduce the morbidity and mortality associated to malaria. Conclusion: Improving household security could help to reduce malnutrition and micronutrients deficiencies in children, contributing to reduce morbidity and mortality associated to malaria. In endemic areas for P. falciparum vitamin A population supplementation has promising results. Studies of zinc are not conclusive and iron has deleterious effects.